Design And Fabrication Of In-House Solar Powered Automatic Irrigation System With Aquaponics’ Concept - Muhammad Badrul Amin, Zulkifli (2022)
This project was aiming to fabricate a downscale system in-house solar powered irrigation system with aquaponics’ concept. Generally, irrigation system is agricultural practice of applying controlled amounts of water to land in order to aid in the production of crops, as well as to grow landscape plants and lawns, where it is known as watering. In connection with the solar energy trends, it is becoming increasingly popular around the world to replace alternative energy sources with conventional energy sources, and the efficiency of obtaining energy from renewable sources. To design this irrigation system, many considerations were taken including the size of the system which play a big role for cost calculation beside the consistency of energy supply from solar PV system and plant growth are the importance parameters to successfully develop this project. The size of the system must be suitable for homeowners. The main objective of this project which was to design and fabricate n-house solar powered irrigation system with aquaponics’ concept was achieved. The fabricated solar powered irrigation system with integration of aquaponics' concept was successfully able to sustain the power supply from solar energy independently for 1 day without The plants and fish inside the aquarium tank can adapt with the aquaponics’ ecosystem without any issue. Also the main components of in-house solar powered irrigation system with aquaponics’ concept. are shown clearly in drawing and its detail was further discussed in this thesis.